Avaliação da sustentabilidade do projeto de Piscicultura Curupati-Peixe no açude Castanhão, Jaguaribara-CE - Nascimento, Sandra Carla Olveira do (2007)
The humanity, until very little time behind, it thought to be the ocean and the water inexhaustible goods and with conditions of provisioning unlimitedly the necessary animal protein to the life. With the growth of the population and the growing demand for food was possible to observe that the alone nature would not be capable to supply those needs. After the decade of 1970, due to overfishing of some important species a new found alternative went commercially to aquaculture. One of the objectives of this work is to answer the aquaculture, as technology of production of victuals of aquatic origin, it can be a sustainable alternative for the solution of the problem mentioned above, using for that a study of case of the project of fish farming Curupati-Peixe installed in the dam Castanhão, Jaguaribara-Ceará. For that it was used as methodology indexes and sustainability degree obtained by three scopes- economicsocial, technological and environmental indicators, everybody these defined and measured for the aquaculture. The method of systems was used as form of capturing the maximum of interrelations among the sub-systems that it composes the sustainable aquaculture. It was observed that the fish farming is shown potentially maintainable, obtaining a medium sustainability (0,603) for the project Curupati-Peixe, being the index of Social Capital (ICS), with value of 0,797, the one that more contributed and the Technological Index (IT), just 0,407, which fewer contributes to that sustainability level.